Hypothesis: A perfect day conveys internal time. (April 2017) - Groß, J.V.; Fritschi, L.; Erren, T.C.
Abstract: In 2007 the International Agency for Research on Cancer [IARC] concluded "shift work that involves circadian disruption is probably carcinogenic to humans" (Group 2A). To investigate the "probable" causal link, information on individual chronobiology is needed to specify exposures to circadian disruption associated with shift work. In epidemiological studies this information is usually assessed by questionnaire. The most widely used Morningness-Eveningness-Questionnaire (MEQ) and MunichChronoTypeQuestionnaire (MCTQ) reveal information on circadian type (MEQ) and actual sleep behaviour (MCTQ). As a further option we suggest to obtain preferred sleep times by using what we call the perfect day (PD) approach. We hypothesize that a PD – as a day of completely preferred sleep behaviour – captures pristine internal time. We argue that the PD approach may measure internal time more accurately than the MEQ and MCTQ which convey influences by work and social time pressures. The PD approach may therefore reduce misclassifications of internal time and reveal circadian disruption caused by different shift systems.